Wireless laptop alarm system - Azree, Musa (2007)
Self conformation system is one of the security system that develop quickly especially on properties security such as home, computer and so on. RFID become one of the conformation technologies that very useful and appropriate to design Wireless Laptop Alarm System. This system used data from the user card, user card will be scan to give the laptop owner’s full permission to excess the laptop. The purpose of this project is to develop a system that can prevent thief problem for laptop users especially in University Malaysia Pahang (UMP). RFID system makes all the services that related with information become easier and safe. Microcontroller MC68HC11 is the main component or brain for the system and it will control by Assembly Language. Assembly program is design so that MC68HC11 be able to conform the data in the card, send the data to the computer and determine the flow of the system. Only user card that get conformation can execute the security application. Besides assembly program, this security system also develops by Visual Basic function. Visual basic function as a guard, it only allow the users to use the laptop if the card users is correct one. When users wish to used the laptop, users must have the right card with the right data. MC68HC11 will receive the data from RFID reader, than MC68HC11 shall filter and process the data. If the data is correct MC68HC11 will transfer the data to visual basic. When visual basic receives the data, laptop window will log in automatically and the users can use the laptop as desired